IMPLEMENTASI METODE EXTREME PROGRAMMING UNTUK PERANCANGAN SISTEM MONITORING KENDARAAN OPERASIONAL BERBASIS WEB ( studi kasus PT. TALKINDO SELAKSA ANUGRAH) - Agung Mursito (PT Triputra Sejahtera Prima, 2023)
The development of information technology has become a daily necessity in our daily lives. We cannot deny that the need for the internet is very much needed. Because the internet has become an inseparable part, as well as in terms of managing data and information that is very much needed. In terms of presentation and management, it must be fast and accurate. Every company, both large and small, engaged in any field, will rely heavily on information technology. This web-based operational vehicle monitoring system is urgently needed at PT Talkindo Selaksa Anugrah. From this system, it is hoped that it can help the operational vehicle management division effectively and efficiently. The method used in designing this educational game uses the Extreme Programming (XP) development method and applications built using the PHP programming language. The results of this study are operational vehicle management monitoring applications that can help the operational vehicle management division effectively and efficiently.